A broadband implantable and a dual-band on-body repeater antenna: design and transmission performance - Kiourti, A.; Costa, J. R.; Fernandes, C. A.; Nikita, K. (IEEE Transactions on Antennas and Propagation, 2014)
The design of a new miniature broadband implantable antenna and a dual–band on–body antenna are presented along with the transmission performance between the two. The former and latter antennas are intended for integration into implantable medical devices (IMDs) and on–body repeaters, respectively. The on–body repeater antenna favors the use of very low power IMDs. The on–body repeater receives low power data from an IMD (MedRadio band, 401–406 MHz) and retransmits it to remote devices placed further apart (ISM band, 2400–2480 MHz). The MedRadio implantable antenna maintains miniature size (399 mm3), and exhibits two close resonances which increase the –10 dB bandwidth inside muscle tissue (87 MHz). The on–body antenna is relatively small (6720 mm3), and exhibits dual resonances in the MedRadio and ISM bands. Assuming a typical arm implantation scenario and an on–body receiver sensitivity of –75 dBm, the proposed configuration is found to enable reduction of the IMD power by a factor of 100. Patient safety and tolerance to electromagnetic interference are, thus, preserved, and lifetime of the IMD is increased. The set–up is, finally, shown to be robust to antenna misalignment and polarization rotation.